Branding dan Pemasaran Kemplang Panggang Desa Tebing Gerinting Selatan Kecamatan Indralaya Selatan - Ardiansyah; Trecy Austin; Suhendra (Yayasan Kawanad, 2022)
In the context of implementing the Tridarma of Higher Education, one of them is through community service as a form of community service. This community service takes the theme of the Thematic Community Service Program